(untitled) (Лучшие интеллектуальные исследования, 2025)
Abstract: This article analyzes the main problems that arise in the popularization of physical education and sports among young people in higher educational institutions. Factors such as the decline in interest in sports among students and the effectiveness of physical education classes are considered. Also, effective solutions are proposed to improve motivation systems for the development of sports, create a modern sports base and strengthen promotional work. The results of the study are intended to be used in the development of strategies aimed at encouraging and developing physical activity in educational institutions.